Catalyst‐Free and Green Synthesis of Some Novel Benzamide Derivatives. (12th December 2014) - Samani Ghaleh Taki, Banafshe; Rostami, Mahbubeh; Mirkhani, Valiollah; Moghadam, Majid; Mohammadpoor‐Baltork, Iraj; Tangestaninejad, Shahram; Jamali Moghadam, Ahmad; Kia, Reza
Abstract : In the present work, a simple, green, rapid, and catalyst‐free procedure for the synthesis of benzamide derivatives byring opening of azlactones with diamines such as ethylene diamine and 1, 3‐propylenediamine is described. The present method offers several advantages such as short reaction times, easy work‐up, and mild reaction conditions in the absence of catalyst and any toxic solvent and material. In addition, the structure obtained by X‐ray crystallography was compared with the theoretical results obtained by density functional theory using the B3LYP functional and cc‐pVDZ basis sets. Abstract :